Financial Performance Analysis of PT Bio farma (Persero) Compare to National, Other Developing Countries, and Global Leading Pharmaceutical manufacturers by Using Most Common Financial Ratios, BUMN Financial Scoring and Moody's Global Pharmaceutical ratin - Raeputranto, Nugraha Yanureza; Damayanti, Sylviana Maya (Journal of Business and Management, 2015)
Abstract. PT Bio Farma as the only one vaccine manufacturer in Indonesia, the first in ASEAN and one of the 30 world companies which gain WHO( World Health Manufacturer ) prequalification certification which considered as the highest standard of quality, faces the tight competition in current vaccine and global pharmaceutical market. As a result, to develop such good strategic, the company needs to assess its performance with one of the option by comparing company’s financial report with existing financial ratios methodology. The methodology using both quantitative and qualitative approaches with uses of three main frameworks to 10 world companies that divided by Indonesia companies, Other Developing Countries and Global Leading Pharmaceutical Manufacturers: 1. Most Common Financial Ratios 2. BUMN Financial Scoring 3. Moody’s Global Pharmaceutical Rating. The result then will be analyzed by qualitative approach to give recommendation for the company. Although Bio Farma considered as the small companies within the samples, in general Bio Farma has outperformed most of the financial ratios above the industries average with the exception of total asset turnover, product theurapetic diversity, revenues and too high of current and cash ratio which indicates the unproductive investment. Example of above ratios are Net Profit Margin 24% (Global 8%), Dupont Analysis 22% (Global 16%), considered as Healthy in BUMN Scoring (Total Score 94%, Global 70%) and obtained Baa1, 7.92 in Moody’s Rating, only below Leading Industries Moody’s Rating Average.Keywords: Financial performance analysis, financial assessment, dupont Analysis, financial ratios, BUMN Scoring, Moody’s Rating.